The Role of Family and Society in Moral Education (Modern education and development, 2025)
This article analyzes the role of family and society in the process of moral education. Moral education is the foundation of personal development, and the influence of the family, as well as the societal environment, is studied in detail. Additionally, the importance of schools, neighborhoods, and mass media in instilling moral values in younger generations is also discussed.